2017
DOI: 10.1111/cas.13240
|View full text |Cite
|
Sign up to set email alerts
|

Cancer with low cathepsin D levels is susceptible to vacuolar (H+)‐ATPase inhibition

Abstract: Vacuolar (H+)‐ATPases (V‐ATPases) have important roles in the supply of nutrients to tumors by mediating autophagy and the endocytic uptake of extracellular fluids. Accordingly, V‐ATPases are attractive therapeutic targets for cancer. However, the clinical use of V‐ATPase inhibitors as anticancer drugs has not been realized, possibly owing to their high toxicity in humans. Inhibition of V‐ATPase may be an appropriate strategy in highly susceptible cancers. In this study, we explored markers of V‐ATPase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Furthermore, protein degradation of macropinocytosed albumin was prevented by treatment with bafilomycin A1 in KRAS -mutant PDAC cells ( 10 ). Interestingly, bafilomycin A1 also inhibits the initial stages of macropinocytosis in HRAS -mutant T24 bladder cells ( 53 ), as well as in KRAS -mutant A549 lung cells ( 54 ). These effects of bafilomycin on nascent macropinosome formation may be a result of either (1) perturbations of cytosolic pH due to impaired pumping of protons into lysosomes or (2) alterations of submembranous pH due to inhibition of proton pumping to the extracellular space.…”
Section: Macropinocytosis and Ph Homeostasismentioning
confidence: 99%
“…Furthermore, protein degradation of macropinocytosed albumin was prevented by treatment with bafilomycin A1 in KRAS -mutant PDAC cells ( 10 ). Interestingly, bafilomycin A1 also inhibits the initial stages of macropinocytosis in HRAS -mutant T24 bladder cells ( 53 ), as well as in KRAS -mutant A549 lung cells ( 54 ). These effects of bafilomycin on nascent macropinosome formation may be a result of either (1) perturbations of cytosolic pH due to impaired pumping of protons into lysosomes or (2) alterations of submembranous pH due to inhibition of proton pumping to the extracellular space.…”
Section: Macropinocytosis and Ph Homeostasismentioning
confidence: 99%
“…4) Previous studies have shown that several metabolic changes take place in the cell during the acquisition of drug resistance. 5,6) Recent advances in both instrumental and computational metabolomic technologies have enabled metabolite profiling studies by NMR spectroscopy, 7) GC-MS, 8,9) LC-MS, 10) and capillary electrophoresis-time of flight (CE-TOF)MS. [11][12][13] As most of the primary metabolites are polar compounds, CE-TOFMS is suitable for separating them from their principle and the superior separation performance is shown by a high theoretical plate number. 14) Even structural isomers (e.g.…”
mentioning
confidence: 99%
“…CTSD protein is a kind of cathepsin. CTSD can directly catalyze the degradation of extracellular matrix and extrabasal membrane, participate in the proteolytic cascade, jointly promote tumor growth, invasion and metastasis [52]. Our research shows that CTSD expression is inversely related to patient survival time.…”
Section: Discussionmentioning
confidence: 68%